Grazing management and silvopasture systems for raising small ruminant production - Mahanta, S.K. (Indian Journal of Agroforestry, 2020)
Small ruminant production is facing a number of grave problems in India. Most important one of them is pressure on grazing resource base, since small ruminant production is primarily based on rangeland grazing. The grazing activity is mainly dependent on the availability of the grazing resources from pastures and other grazing lands. The grazing intensity in the country is as high as 12.6 adult cattle units (ACU)/ha as against 0.8 ACU/ha in developed countries. Hence, the task to deal with such situation is two-fold (i) improvement of pastures, and (ii) judicious implementation of grazing management. Silvopasture system has been recommended to optimize, rather than maximize, production (both pasture and animal) from the same unit of land through integrated management. Studies indicated that body weight gains in lambs and kids were higher when grazed on silvopastoral system over natural grassland. It was even observed that double number of animals can be reared on silvopasture than that of natural grassland under similar unit of lands. Again choice of grazing management affects pasture yield, nutritive value, and stand longevity. Choice of grazing management also affects weight gain or milk production of an individual animal as well as the amount of milk or meat produced per hectare. In order to implement an effective grazing management program, there are a number of important issues, which should be kept in mind. These include a) what is required for plants and animals to be productive in a pasture-livestock system, b) what management choices have the greatest impact on success or failure of a grazing system, and c) how can the nutritional requirements of the animal be matched with the ability of the pasture to supply nutrients. It was observed that improved grazing management practices like rotational or deferred rotational had comparatively better performances over continuous system of grazing in terms of less soil as well as nutrient loss, improved soil fertility status, higher herbage biomass and animal production.